Out of the Closet and into Quarantine: Stories of Isolation and Teaching - Forrest, Michelle; Joy, Phillip (Atlantis, 2021)
Being queer can be filled with moments of isolation: not fitting in to heteronormative rites of passage, not knowing if or when to come out in academia, and now, trying to cope with the difficulties induced by officially-mandated social distancing in a global pandemic. Although isolation is a common human experience, for queer people it is often an intimate part of their stories, leaving lasting scars. Experiences of isolation, loneliness, and being “othered” have serious consequences. Through autoethnographic queer inquiry, we explore isolation and how it shapes teaching and learning. Drawing on concepts of the outsider-within and the uncanny, and distinguishing isolation from loneliness and solitude, we share our personal stories of isolation through the perspective of a performative “I”, examining how our pedagogical philosophies and practices inevitably reflect our queer experiences. Coming from different disciplines of practice, we met because of the COVID-19 pandemic, which prompted this return to old and new forms of social isolation—the old being the experience of growing up queer and the new through teaching online. From our perspectives across a generational divide, we trace the unsettling experiences of being queer and teaching in our COVID bubbles, and we attempt to navigate ourselves and our students safely through disconnection and isolation.